Édifier et instruire : une typologie des restaurations exposées à Paris autour de 1750 - Noémie Étienne (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The exhibition of restoration has a current events but also an history. This article has for objective to remind some elements of this story by drawing up brief archaeology of these practices in Paris around 1750. These exhibitions take on variable economic and political stakes.